The Correlation between Students’ Writing Skills and Speaking Skills - Fadli Faisal Rahman; Bradhiansyah Tri Suryanto (International Journal of English Education and Linguistics (IJoEEL), 2022)
Some English learners might be very good at speaking English but not optimal in writing English, and vice versa. However, there were also some English learners who have almost the same score between writing and speaking skills. As fellow productive language skills, researching the relationship between writing skills and speaking skills will be very interesting. Based on the phenomena that exist in the field when reviewing the results of foreign language skills, especially English, the researchers tried to map the relationship between writing skills and speaking skills in English owned by learners, especially English learners in universities. It became very interesting to reveal the relationship between two different English skills through research with a correlation research design. This research was conducted with the aim of knowing the correlation between English writing skills and English speaking skills possessed by students. The design of this research is correlation research. The subjects of this study were 49 fifth semester students of the English Education Study Program, Nurul Jadid University, Probolinggo, in the 2021-2022 academic year. In the fifth semester the students took advanced writing courses and advanced speaking courses. From the results of the calculation of correlation analysis could be revealed that the correlation coefficient (rxy) is 0.0776. With an alpha value between 0.05 and 0.95, the t-table value is 1.6779, and the t-count value was 0.5338. From the results of this study, it could be stated that English writing skills and English speaking skills possessed by students had a very weak positive correlation. In other words, it could be stated that the higher the value of writing skills, the higher the value of students' English speaking skills with a very weak correlation.